1997
DOI: 10.1002/(sici)1096-9071(199711)53:3<205::aid-jmv4>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Identification and typing of molluscum contagiosum virus in clinical specimens by polymerase chain reaction

Abstract: A polymerase chain reaction (PCR) which enables the detection of molluscum contagiosum virus (MCV) genomes in either fresh or formalin-fixed clinical specimens is described. The primers used were designed to amplify a 167 bp region of the 3.8 kbp HindIII fragment K of the MCV 1 genome. The ability of this PCR to detect three common MCV types (1, 1v and 2) in clinical specimens was confirmed using frozen extracts from 75 molluscum lesions, and digests of single sections of 11 formalin-fixed, paraffin-embedded l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…The use of PCR to identify MCV infection (Nunez et al, 1996;Thompson, 1997) and the use of restriction mapping or hybridization to characterize the subtypes (Darai et al, 1986;Porter et al, 1987;Thompson, 1997) has been previously reported. Although these are functional assays, they are not without their limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of PCR to identify MCV infection (Nunez et al, 1996;Thompson, 1997) and the use of restriction mapping or hybridization to characterize the subtypes (Darai et al, 1986;Porter et al, 1987;Thompson, 1997) has been previously reported. Although these are functional assays, they are not without their limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Though this virus cannot be cultured, other diagnostic modalities include electron microscopy, immunohistochemistry using polyclonal antibody and in-situ hybridization for in-situ DNA. 4,8,9 MC presenting as a cutaneous cystic lesion simulating a SC is an extremely rare entity and literature review showed only one such case being reported, to the best of our knowledge. Al-Hilo et al carried out a study on different clinical presentations of MC in Iraqi patients, which demonstrated 28 out of 330 patients (8.48%) with an atypical presentation.…”
Section: Introductionmentioning
confidence: 90%
“…Similarly, PCR assays were established that amplified OPV with species-specific amplicon lengths [70]. Some notable conventional PCR assays have been published for other human poxviruses [43,[71][72][73][74][75]]. …”
Section: Polymerase Chain Reactionmentioning
confidence: 99%